IMPLEMENTASI PROGRAM MERDEKA BELAJAR PADA PEMBELAJARAN AQIDAH AKHLAK DALAM MENGEMBANGKAN KREATIVITAS PESERTA DIDIK DI MTS HIDAYATUL MUBTADI’IN TASIKMADU MALANG - Wahdina Salim Aranggere; Dian Mohammad Hakim; Syamsu Madyan (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
The Independent Learning Program is a new policy from the Ministry of Education andCulture Research Technology that wants to create pleasant learning conditions, bothfor teachers and students. According to Nadiem Makarim, independent learning meansthat educational units, namely schools, teachers and students have the freedom toinnovate and act in the learning process. There are four policies in independentlearning, namely USBN in exchange for assessment, in 2021 the UN is replaced, RPP isshortened and PPDB zoning is more flexible. The purpose of this study was todetermine the planning, implementation and evaluation of the independent learningprogram in Aqidah Akhlak learning in developing students' creativity. This researchwas conducted at MTs Hidayatul Mubtadi'in Tasikmadu Malang. This research wasconducted using a qualitative approach. Data were collected using in-depthinterviews, participant observation and documentation. Then, the data analysismethod uses the Miles and Hubberman method. The results showed that thecurriculum used was an emergency curriculum, using a one-page lesson plan and thenevaluating learning using test and non-test assessments as well as the habituation ofthe Religious Culture Program to help support the creativity of students at MTsHidayatul Mubtadi'in Tasikmadu Malang.